Project Based Learning Model in Computer Programming Courses at Mathematics Student - Gusmi Kholijah; Niken Rarasati; Corry Sormin; Fazar Aryanto (IJER (Indonesian Journal of Educational Research), 2023)
Project-based learning is carried out for computer programming courses. In this lesson, students are expected to have skills in recognizing, constructing, and creating programs from a problem using a programming language. This is a research and development (R&D) that consist of team based project scheme stage, development stage, implementation stage, and final or evaluation stage. When making a computer program on a problem, students must be able to identify the required input, process, and output. Then the information is constructed in an algorithm which is then made into a computer program. Its implementation there are schemes that have been implemented, namely: the preparation stage, and the project work activity process, which includes; forming groups, case studies, gathering information on project-based activities, and producing documentation and portfolios of project implementation and evaluation. This research also produces products in the form of graduate learning outcomes (CPL), Syllabus and Lecture Contracts, Semester Learning Plans (RPS), Student Project Task Plans (RTM) or Student Project Worksheets (LKM), Learning Outcomes Assessment Sheets (LPHB) in accordance with project-based learning model (Project Based Learning). The results of the evaluation through a questionnaire obtained that student perceptions of computer programming courses were very high.